Referências culturais e heterogeneidade discursiva :Uma proposta para o ensino-aprendizagem de língua inglesa - Canan, Ana Graça (2007)
The purpose of this research is to approach the English literary text from the point of view of the culture and the heterogeneity of discourse in its role as a source of elements that facilitate the teaching/learning process of English as a foreign language. Several instances of discourse heterogeneity are analyzed through cultural references in the original texts of the following English novels: Jane Eyre, by Charlotte Brontë (1816-1855), published in 1847; The Mill on the Floss, by George Eliot (1819-1890), published in 1860 and Great Expectations, by Charles Dickens (1812-1870), published between 1860 and 1861. Theoretical support was sought in Kramsch, Bakhtin, Maingueneau, Authier-Revuz, Widdowson and Larsen-Freeman. Activities in English are proposed in the end whereby it can be seen that the questions at issue can be used extensively in the classroom.